Effects of Mechanical Stress Stimulation on Function and Expression Mechanism of Osteoblasts - Liu, Pan; Tu, Ji; Wang, Wenzhao; Li, Zheng; Li, Yao; Yu, Xiaoping; Zhang, Zhengdong (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoclasts and osteoblasts play a major role in bone tissue homeostasis. The homeostasis and integrity of bone tissue are maintained by ensuring a balance between osteoclastic and osteogenic activities. The remodeling of bone tissue is a continuous ongoing process. Osteoclasts mainly play a role in bone resorption, whereas osteoblasts are mainly involved in bone remodeling processes, such as bone cell formation, mineralization, and secretion. These cell types balance and restrict each other to maintain bone tissue metabolism. Bone tissue is very sensitive to mechanical stress stimulation. Unloading and loading of mechanical stress are closely related to the differentiation and formation of osteoclasts and bone resorption function as well as the differentiation and formation of osteoblasts and bone formation function. Consequently, mechanical stress exerts an important influence on the bone microenvironment and bone metabolism. This review focuses on the effects of different forms of mechanical stress stimulation (including gravity, continuously compressive pressure, tensile strain, and fluid shear stress) on osteoclast and osteoblast function and expression mechanism. This article highlights the involvement of osteoclasts and osteoblasts in activating different mechanical transduction pathways and reports changings in their differentiation, formation, and functional mechanism induced by the application of different types of mechanical stress to bone tissue. This review could provide new ideas for further microscopic studies of bone health, disease, and tissue damage reconstruction.